PENGARUH LITERASI DAN PERENCANAAN KEUANGAN TERHADAP PERILAKU KEUANGAN DENGAN TINGKAT PENDIDIKAN SEBAGAI VARIABEL INTERVENING PADA UMKM KULINER BINAAN BRI KANWIL MAKASSAR - Kurniawan, Ahmad Reza; Mappamiring, Mappamiring; Alam, Syamsul (Bussman Journal : Indonesian Journal of Business and Management, 2024)
The Influence of Financial Literacy and Financial Planning on Financial Behavior with Education Level as an Intervening Variable in In Culinary Umkm Guided by Bri Makassar Regional Office. Supervised by Mappamiring and Syamsul Alam. This study aims to determine the direct effect of financial literacy variables, financial planning and education level on financial behavior and financial literacy and financial planning on education level in Food and Beverage MSMEs Registered at BRI Makassar City. Data collection uses primary data obtained from questionnaires using saturated samples. The population in this study was 100 respondents. The results of the questionnaire have been tested for validity and reliability using the PLS model scheme and model evaluation, inner model evaluation with determinant coefficient tests, model goodness of fit tests and hypothesis tests both directly and indirectly. The results of this data processing use SmartPLS version 3. The results of the study directly show that the variables of financial planning and education level have a positive and significant effect on financial behavior, financial literacy does not affect the level of education and financial behavior, financial planning has a positive and significant effect on the level of education. The results of the study indirectly show that literacy does not affect financial behavior with the level of education as an intervening. Financial planning has a positive and significant effect on financial behavior with the level of education as an intervening